Efecto de la mezcla de micro-fibras y macro-fibras polimerícas en el comportamiento a flexión y compresión del UHPFRC (2020)
The constant advancement of science and technology has allowed the development of special concretes such as ultra-high-performance concrete (UHPC). To counteract the fragility of these concretes, and in turn, to improve the mechanical conditions of the same, the incorporation of fibers is common, thus generating ultra-high-performance fiber reinforced concrete (UHPFRC). UHPFRC has greater durability, ductility, strength and toughness compared to conventional concrete or fiber-reinforced concrete (FRC) due to its low porosity and the densification of its matrix. The addition of fibers to the densified matrix allows to develop an acceptable direct tensile and flexural behavior. Over time, research related to the behavior of UHPFRC has agreed that the hybrid mixture of fibers allows optimizing the mechanical performance of this composite material. However, research has also shown that the incorporation of steel fibers into the matrix greatly increases the initial cost of UHPFRC, along with the high dosages of cement and silica fume required to obtain a dense matrix. Consequently, the high cost, the recent incursion of the material and the lack of guidelines indicating its structural design parameters have limited a wider spread of UHPFRC in Latin America. Aware of this problem, the present document presents the results of a research project that evaluated the effect of the mixture of polymeric micro and macro-fibers on the flexural and compressive behavior of the UHPFRC. For this reason, it was necessary and pertinent to develop an experimental program to evaluate the behavior of the UHPFRC reinforced with polymeric fibers. In the experimental program, 36 dosages were elaborated, with which it was sought to demonstrate that the flexural and compression behavior of the UHPFRC reinforced with polymeric fibers can be similar or better in some cases, to the flexural and compression behavior of the UHPFRC reinforced with steel micro-fibers. The dosages presented the following variables and fiber proportions: • 2 dosages of UHPC were made to achieve the adequate static flow of the standard mix. • 2 dosages of UHPFRC were reinforced with 1 or 2% of steel micro-fibers (OL 13/.20) in volume. These dosages allowed to compare the results obtained by the dosages of UHPFRC reinforced with polymeric fibers with the same volume fiber content. • 32 dosages of UHPFRC were reinforced with micro and/or macro polymeric fibers. The micro-fiber (mF) material was nylon or alcohol polyvinyl and the macro-fiber (MF) material was polypropylene or a mixture of polypropylene and polyethylene. The proportion of polymeric fibers by volume was as follows: 1.0% fiber by volume 2 mixes with (1% - mF) 4 mixes with (0.75% - mF y 0.25% - MF) 4 mixes with (0.5% - mF y 0.5% - MF) 4 mixes with (0.25% - mF y 0.75% - MF) 2 mixes with (1% - MF) 2.0% fiber by volume 2 mixes with (2% - mF). 4 mixes with (1.5% - mF y 0.5% - MF) 4 mixes with (1% - mF y 1% - MF) 4 mixes with (0.5% - mF y 1.5% - MF) 2 mixes with (2% - MF) The results allowed to observe that the UHPFRC specimens reinforced with 1.5 or 2% of polymeric macro-fibers in volume, showed an outstanding flexural behavior. It was even similar to the flexural behavior of the specimens reinforced with 1 or 2% steel micro-fibers. In addition, when making a technical-economic comparison of the mechanical properties of UHPFRC, it was shown that UHPFRC specimens reinforced with 2% polymeric macro-fibers by volume have the best cost-benefit ratio in terms of energy absorption capacity. It refers, in comparison to the cost benefit offered by the specimens reinforced with 2% of steel micro-fibers in volume. However, it was observed that the specimens reinforced with 2% of polymeric macro-fibers by volume absorb only 79% of the energy absorbed by the specimens reinforced with 2% of steel micro-fibers in volume. Finally, the results showed that the compressive strength of UHPFRC specimens reinforced with 0.75 or 1% of polymeric micro-fibers by volume, are capable of withstanding 14% more compressive load compared to UHPC specimens. Furthermore, this compressive strength was similar to that obtained by UHPFRC specimens reinforced with 1 or 2% steel micro-fibers by volume.